Teacher Performance Assessment Development Management In Smart Society 5.0 Era - Aji Wahyudin; Nazhatuz Zaman; Asiyah Khoirun Nisak; Indah Aminatuz Zuhriyah (Mudir : Jurnal Manajemen Pendidikan, 2023)
This study aims to discuss teacher performance appraisal. This research method is descriptive qualitative. The results of the study show that Teacher Competency Standards in the era of smart society 5.0 are fully developed from 4 main competencies, namely pedagogic, personality, social, and professional competencies. The fourth competency is integrated with teacher performance. There are indicators of teaching skills by teachers namely, a) questioning skills; b) skills to provide reinforcement (reinforcement skills); c) the skill of making variations; d) explaining skills ( explaining skills); e) skills to open and close lessons (set induction and closure skills); f) skills in guiding small group discussions; g) class management skills; h) individual learning skills. In conclusion, teacher performance has certain specifications or criteria. Teacher performance can be seen and measured based on specifications or competency criteria that must be owned by each teacher.